The rising - Graham, Heather; Land, Jon (Tor, 2022)
Twenty-four hours. That's all it takes for the lives of two young people to be changed forever. Alex Chin has the world on a plate. A football hero and homecoming king with plenty of scholarship offers, his future looks bright. His tutor, Samantha Dixon, is preparing to graduate high school at the top of her class. She plans to turn her NASA internship into a career. When a football accident lands Alex in the hospital, his world is turned upside down. His doctor is murdered. Then, his parents. Death seems to follow him wherever he goes, and now it's after him. Alex flees. He tells Samantha not to follow, but she became involved the moment she walked through his door and found Mr. and Mrs. Chin as they lay dying in their home. She cannot abandon the young man she loves. The two race desperately to stay ahead of Alex's attackers long enough to figure out why they are hunting him in the first place. The answer lies with a secret buried deep in his past, a secret his parents died to protect. Alex always knew he was adopted, but he never knew the real reason his birth parents abandoned him. He never knew where he truly came from. Until now.